Ethics and the nature of moral philosophy - Moore, G. E. (George Edward), 1873-1958 (British moral philosophers., 2005)
G.E. Moore's 1912 work Ethics has tended to be overshadowed by his famous earlier work Principia Ethica. However, its detailed discussions of utilitarianism, free will, and the objectivity of moral judgements find no real counterpart in Principia, while its account of right and wrong and of the nature of intrinsic value deepen our understanding of Moore's moral philosophy. Moore himself regarded the book highly, writing late in his career, "I myself like [it] better than Principia Ethica, because it seems to me to be much clearer and far less full of confusions and invalid arguments." Short but philosophically rich, and written with impressive precision and intellectual candor, Ethics is a minor classic which repays careful study. This new edition includes Moore's essay "The Nature of Moral Philosophy" as well as editorial notes, an introduction, and a guide to further reading.